An Investigation of Antimicrobial Activity of Celery (Apium graveolensis L.) - DOSTBIL, NURSEL (Asian Journal of Chemistry, 2010)
In this study, the antimicrobial activity of celery (Apium graveolensis L.) has been reported. The extract of celery were prepared in diethyl ether and tested against P. aeruginosa ATCC 27853, E. coli ATCC 25922, K. pneumonia FML 5, S. aureus ATCC 25923, M. smegmatis CCM 2067, M. luteus A 2971 ve C. albicans ATCC 60192 with the disc diffusion method. Celery had inhibitory activity on K. pneumoniae FML 5, M. smegmatis CCM 2067, M. luteus A 2971, S. aureus ATCC 25923 and C. albicans ATCC 60192 but has no inhibitory activity against other bacteria strains.